Oil as matter, oil as discourse: Tom McCarthy's Satin Island. Issue 2 (3rd April 2019) - Grewe-Volpp, Christa
ABSTRACT: A pertinent example of the energy unconscious in petrofiction is Tom McCarthy's Satin Island, in which an oil spill is one of the dominant motifs. One central question the novel raises is how oil as matter functions in this text which is heavily influenced by poststructuralist theory. The main protagonist U searches for the meaning of oil in a thoroughly digitized and mediated world, in which his grasp of the world depends on pixelated images. His fascination with an oil spill is an apt example of how a purely discursive reading of oil misses its agentic influence on Western culture as well as culture's implications in the accident of an oil spill. An interpretation of the oil spill as a sign of the energy unconscious reveals the novel's reflection on the shortcomings of a purely poststructuralist reading of culture and asserts the relevance of a new materialist reading.